Implementasi Projek Penguatan Profil Pelajar Pancasila di Sekolah Dasar - Amaliyah, Nurrohmatul; Kosasih, Kosasih; Hamid, Zamroni; Karlinah, Alin (Universitas PGRI Semarang, 2025)
This research aims to find out what the results of the implementation of project strengthening the Pancasila student profile (P5) will be if implemented in elementary schools. In the independent curriculum currently used, every school is required to maintain good national character and norms so that the Pancasila student profile is strengthened. This research uses a qualitative approach. The qualitative approach was chosen based on various considerations, including the problems studied regarding the concept of character education in the Pancasila student profile for elementary school teachers. The researcher decided to use the phenomenological method with a qualitative approach as the method used in this research. The phenomenological method was chosen because this research aims to study participants' understanding of meaningful experiences in their lives and examine the experiences in their own situations. The results of this research were the discovery of several supporting and inhibiting factors for the implementation of the Pancasila student profile in the elementary school environment.